A Qualitative Study of Children’s Accounts of Cruelty to Animals: Uncovering the Roles of Trauma, Exposure to Violence, and Attachment - Wauthier, Laura (Journal of interpersonal violence, 2022)
Childhood animal cruelty (CAC) is a risk for later interpersonal violence and a red flag for other forms of violence in the household, yet very few studies have spoken to children directly about their cruelty to animals. Animal Guardians (AG) is a humane education program run by the Scottish SPCA for children of age 5 to 12 years who have been cruel to animals or deemed at-risk. This research investigated how children referred to AG spoke about their experiences of animal cruelty and factors surrounding it. Research consent was obtained for 10 children (average age?=?8.8 years, n?=?9 males), referred concerning cruel/at-risk behavior toward their pets. The interview schedule combined techniques such as crafts, vignettes, open questions, and standardized measures. Interviews were qualitatively analyzed using content analysis and interpretative phenomenological analysis (IPA). Content analysis suggested that referred children (a) tended to have small attachment networks which often included pets, (b) tended to interpret ambiguous situations predominately negatively, (c) tended to like animals and see them as sentient, and (d) struggled admitting to cruelty. Three main superordinate themes emerged from the IPA: (a) Bonding to animals, (b) Exposure to/normalization of violence, and (c) Signs of emotional issues/trauma. Children who were referred for animal cruelty toward their pets were from vulnerable backgrounds, often had complex backdrops to their at-risk or cruel behavior, and sometimes had trouble regulating their emotions and behaviors. Programs hoping to address CAC should be aware of these complex emotional, psychological, and behavioral factors, tailoring interventions accordingly.